Actinomycosis of eye: Forgotten but not uncommon. (October 2015) - Mehrotra, Neha; Baidya, Ankita; Brijwal, Megha; Aggarwal, Rita; Chaudhry, Rama
Abstract: Actinomyces species are known to cause a variety of human infections. Ocular actinomycosis is a rare disease. We report an unusual case of bilateral actinomycotic blepharoconjunctivitis in the absence of canaliculitis that presented with forniceal masses in eye. The case report is discussed here along with Indian literature. Highlights: We report a case of bilateral chronic blepharoconjunctivitis caused by Actinomyces israelii . The patient responded to topical antibiotics and had good visual outcome. A. israelii is an anaerobe gram positive bacilli, which occur as normal flora in animals and humans. Ocular actinomycosis is rarely reported.